Are we any closer to understanding why fish can die after severe exercise?. Issue 6 (7th August 2022) - Holder, Peter Elliot; Wood, Chris M.; Lawrence, Michael J.; Clark, Timothy D.; Suski, Cory D.; Weber, Jean‐Michel; Danylchuk, Andy J.; Cooke, Steven J.
Abstract: Post‐exercise mortality (PEM) may occur when fish exercise to exhaustion and are pushed so far beyond their physiological limits that they can no longer sustain life. Although fish exercise to overcome a variety of natural challenges, the phenomenon of PEM is most often observed as the result of interactions between fish and humans. The seminal work of Black (Can J Fish Aquat Sci, 15:573, 1958) and Wood et al. (J Fish Biol, 22:189, 1983) provided a foundation for exploring the potential causes of PEM in fish. With no "silver bullet" explaining PEM being apparent, contemporary research has continued to focus on physiological mechanisms of exhaustion in fish, including factors such as oxygen delivery, ion regulation, hormone signalling, and cardiac function. This paper provides an overview of these studies, and reviews the continuous improvement in data collection methods, tools, and experimental protocols used to examine the PEM phenomenon. These studies of exhaustion have played an important role in informing management actions for activities such as bycatch revival and fish passage. Since the contribution of Wood et al. (Journal of Fish Biology, 22(2):189–201, 1983), the combined efforts of fundamental and applied research have yielded a greater understanding of why fish die after severe exercise, yet much remains to be explored through future work.